Causes of Vomiting in Hospitalized Children - Frankul, Fairs M.; Fahmi, Nariman; Basil, Dalia (Journal of the Faculty of Medicine Baghdad, 2007)
Background: vomiting is a very common symptom of disease in childhood, it occurs both in gastrointestinal and non-gastrointestinal diseases. Objectives: Our aim of the study was to find out the causes of vomiting in different age group, the improper management of vomiting in daily practice and to emphasis on the usefulness of imaging study in the diagnosis. Methods: A prospective study was carried out on patients presented with vomiting admitted to Children Welfare Teaching Hospital from the first of Dec. 2001 to the end of April 2002 .The age ranged between early neonatal periods to 12 years of age. Reults: A total of 100 child were included in this study,(65) male (35) female male to female ratio was1.86:1. Surgical causes of the gastrointestinal tract was the most common cause of vomiting (50 %) in the neonatal period, while infectious cause formed 78.3% & 48.4% during infancy and childhood respectively. Imaging studies was carried out on 54 patients and helped to reach a final diagnosis in 21(38,9% ) patients. In this study green color vomiting was found to relate mainly (64.7%) to the intestinal obstruction with a (p) value >0.05. Conclusion: There was no benefit of antiemetic drugs in the treatment of vomiting, Imaging studies were helpful in reaching the correct diagnosis of vomiting in some cases, green color vomiting should make pediatrician suspicious of intestinal obstruction.